Work-Life Balance in the Teaching Profession: Insights from a Decade of Scholarly Research - Moh. Badrut Tamam (Suria Academic Press, 2026)
The balance between professional and personal life among educators has become a critical issue as teaching demands, administrative workloads, and technology driven tasks increasingly blur the boundary between work and home life. This study maps the development, intellectual structure, and themes of teacher work life balance research over the last decade using a bibliometric approach. Previous bibliometric studies on work life balance have generally remained cross sectoral and generic, with limited attention to the occupational specificity and institutional realities of teachers. Data were retrieved from Scopus and analyzed using VOSviewer and Biblioshiny in RStudio. From an initial corpus of 297 records, 160 publications published between 2015 and 2025 were selected through inclusion exclusion criteria and the PRISMA flow. The results show an increase in publication output, with a rise in 2023 and 2024 and stabilization in 2025, indicating field maturation. Frontiers in Psychology was the leading source, while the United States and China contributed the citation impact. Keyword co-occurrence analysis identified dominant themes including teachers, work life balance, job satisfaction, burnout, and stress, organized into five connected clusters, with survey and cross-sectional designs prevailing. This article uniquely contributes to education literature by offering a teacher centered bibliometric map that clarifies the intellectual structure, thematic evolution, and policy relevant directions of work life balance research. The findings position teacher work life balance as a structural educational issue, not merely an individual coping problem, and support institutional and policy interventions to manage workload, strengthen welfare support, and sustain teacher retention.